Analisis Strategi Product Mix Pada Produk Multi Varian Dalam Meningkatkan Kinerja Penjualan Di Industri Frozen Food (Studi Kasus: CV Marala Food) Kab. Gowa Sulawesi Selatan - Aidil Azwar; Akmal Abdullah; Sulkifli Sulkifli (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The growth of the frozen food industry in Indonesia, driven by shifting consumer lifestyles, has intensified business competition and compelled companies to adopt effective marketing strategies. A key strategy is the product mix the management of a product combination encompassing width, length, depth, and consistency within the product portfolio. This study aims to assess the sales performance of frozen food products at Marala Food and analyze the impact of the product mix strategy on the company's sales performance. A quantitative, survey-based research design was employed. Primary data were collected via questionnaires distributed to a sample of 50 respondents selected through purposive sampling, while secondary data were obtained from the company's sales reports for the period of August–December 2025. Data analysis involved validity and reliability testing, classical assumption testing, and multiple linear regression analysis using SPSS software. The findings confirm that the majority of measurement instruments met validity and reliability criteria. Marala Food's sales performance showed an upward trend during the study period, with peak sales occurring in December 2025. Regression analysis revealed that the product mix strategy made a positive and significant contribution to sales performance. The coefficient of determination (R²) of 0.868 indicates that 86.8% of the variation in sales performance can be explained by the variables of product mix width, length, depth, and consistency.